The use of Malaysian herbs for female sexual dysfunction among women in Pahang, Malaysia - Abdul Ghani, Radiah; Bakri, Siti Aishah; Hassan, Hadijah (2022)
Female sexual dysfunction (Mati Putik) is a disorder related to sexual desire, arousal, and orgasm among women and the prevalence worldwide has reached 12% in 2020. Traditional medicine such as herbal consumption is a common alternative to treat or prevent female sexual dysfunction (FSD). As recorded in the Malay Medical Manuscripts, Manjakani, Halba, Adas Pedas, Zafaran, and Sirih were herbs described to treat FSD and thus is the focus of this study. Even the use of herbs has become a trend nowadays, however the knowledge regarding the herbs among the users in Malaysia is inconclusive. Hence, this study aimed to investigate the knowledge, attitude and practice (KAP) on herbs used to treat FSD among women in Kuantan, Pahang. A cross-sectional study was conducted in Kuantan, Pahang between April 2021 and July 2021. A total of 91 respondents were recruited among women that fulfilled the inclusion and exclusion criteria for this study. Convenience sampling has been done for this study and self-administered online questionnaires were distributed among the respondents. All the data from the respondents were analysed through the statistical package for social sciences (SPSS) (IBM SPSS Statistic 20). This study shows that the respondents had low knowledge (n=86; 94.5%), moderate attitude (n=62: 68.1%), and low practice (n=68; 74.7%) on usage of herbs for FSD. There were significant association has been detected by using Kruskal-wallis test in terms of occupation with the practice score of the respondents. A significant correlation was identified using Spearman coefficient between knowledge and attitude (r=0.309, p=0.003) and knowledge and practice (r=0.435, p<0.001) of the respondents. It is recommended to have more future studies in relation to the knowledge attitude and practice on the usage of herbs among women who were diagnosed with FSD especially in larger community. In future, these studies will result in promoting further initiatives to strengthen the knowledge and give a right guidance on the usage of herbs among women for them to lead a better quality of life